The Characteristics of Pineapple Probiotic Drinks Enriched by Inulin’s Mangrove (International Journal of Scientific Research and Management (IJSRM), 2024)
Probiotic drinks are functional drinks made from the fermentation process of Lactic Acid Bacteria (LAB). This drink usually uses milk-based ingridients, but diversification of vegetable-based products is carried out with pineapple because it contains sugar, vitamin, and has an attractive color and aroma. The probiotic drink was enriched by Inulin’s mangrove apple. The research aims to determine the Characteristics of pineapple probiotic drink enriched by inulin’s mangrove apple. The research procedures carried out were making pineapple juice, inulin’s mangrove apple, and pineapple fruit probiotic drink which enriched by inulin’s mangrove apple. The concentration of Inulin’s mangrove apple was significant (p<0.05) on the characteristics of pineapple fruit probiotic drinks. The pH valus of 3.70-4.10, total sugar 9.30-10.53o brix, and total LAB 9.5 x 107 -4.33x 108 CFU/mL. There was a significant effect (p<0.05) on the aroma, taste and overall variables in the hedonic test results and no significant effect on the color. THe concentration of 3% inulin’s mangrove apple is the best.